Sifat Inovasi Padi Sawah Varietas Inpari di Desa Gunung Sari Kecamatan Bonegunu Kabupaten Buton Utara - Suwiati Karim; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2022)
This research is motivated by the innovative nature of the variety of lowland rice. This study aims to determine the nature of the innovation of Inpari variety of lowland rice in Gunung Sari Village, Bonegunu District, North Buton Regency. This research was conducted in Gunung Sari Village, Bonegunu District, North Buton Regency, which was carried out in May-June 2021 using a quantitative descriptive method with a total of 27 farmers of inpari rice varieties in Gunung Sari Village. The data analysis model used in this study is the class interval model. The results showed that the innovative nature of the inpari variety of lowland rice in Gunung Sari Village, Bonegunu District, North Buton Regency was included in the high category with a percentage of 100% in other words thst the innovative nature of inpari variety rice in Gunung Sari Village could be developed, and sait very well.